2020
DOI: 10.1111/ijcp.13750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index on oncological and surgical outcomes in patients undergoing radical cystectomy for bladder cancer: A multicentre study of the association of urooncology, Turkey

Abstract: Objective We aimed to evaluate the effect of body mass index (BMI) on oncological and surgical outcomes in patients who underwent radical cystectomy (RC) for bladder cancer (BC). Materials and Methods We retrospectively assessed data from patients who underwent RC with pelvic lymphadenectomy and urinary diversion for BC recorded in the bladder cancer database of the Urooncology Association, Turkey, between 2007 and 2019. Patients were stratified into three groups according to the BMI cut‐off values recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Interleukin-4 (IL-4), a cytokine is produced by T cells and induces activation of B cells and lymphocytes, thus providing inhibition of angiogenesis, as well as activation of granulocytes and eosinophil, and surveillance and clearance of tumor cells (Swain et al 1990;Olver et al 2007;Izol et al 2021). IL-4 gene resides on the 5q31.1 chromosome in a cytokine gene cluster (Duan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-4 (IL-4), a cytokine is produced by T cells and induces activation of B cells and lymphocytes, thus providing inhibition of angiogenesis, as well as activation of granulocytes and eosinophil, and surveillance and clearance of tumor cells (Swain et al 1990;Olver et al 2007;Izol et al 2021). IL-4 gene resides on the 5q31.1 chromosome in a cytokine gene cluster (Duan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large body of evidence demonstrating an association between obesity and surgical morbidity, conflicting reports exist regarding complication risk from obesity subcategories. Izol 10 and Lenardis 11 et al reported that major complications are more common in obese patients than in over- and normal-weight patients after RC. At the same time, a systematic review indicated that complication risk was increased in both overweight and obese BMI categories.…”
mentioning
confidence: 99%